Mining intelligence and knowledge exploration : 4th International Conference, MIKE 2016, Mexico City, Mexico, November 13-19, 2016, Revised selected papers /: 4th International Conference, MIKE 2016, Mexico City, Mexico, November 13-19, 2016, Revised selected papers. (2017) - Unknown
No abstract available